Relationship between floor type and risk of ACL injury in team handball - Olsen, O. E.; Myklebust, G.; Engebretsen, L.; Holme, I. (Scandinavian Journal of Medicine & Science in Sports, 2003)
The purpose of this study was to compare the ACL injury rate between two different floor types - wooden floors (parquet, generally having lower friction) and artificial floors (generally having higher friction). ACL injuries have been recorded prospectively from the three top divisions for men and women in Norwegian team handball during seven seasons (1989-2000). A total of 174 ACL injuries have been recorded, and of these 53 occurred in regular league games. The floor types for all regular games from the same seasons have been determined retrospectively based on match schedules. The matches were divided into two groups: those played on wooden floors and those played on artificial floors. A total of nine injuries occurred among men (incidence: 0.24±0.09 injuries per 1000 player hours) and 44 among women (0.77±0.04 injuries 1000 h1; OR vs. men: 3.21 (1.56-6.58); P=0.001). Among men, four injuries occurred on wooden floors (0.32±0.13 injuries 1000 h1) and five injuries occurred on artificial floors (0.20±0.12 injuries 1000 h1; OR vs. wooden floors: 0.63 (0.17-2.37); ns). Among women, eight injuries occurred on wooden floors (0.41±0.09 injuries 1000 h1; OR vs. men: 1.29 (0.39-4.28); ns) and 36 on artificial floors (0.96±0.04 injuries 1000 h1; OR vs. wooden floors: 2.35 (1.09-5.07); P=0.03; OR vs. men: 4.77 (1.87-12.18); P=0.001). These results indicate that the risk of ACL injury for women is higher on artificial floors than on wooden floors.